A descriptive and stereotypical study of the ancient amphorae displayed in the Annaba Museum (Hippon). - amaj, belkacem (Journal of Social Sciences and Humanities, 2025)
This study aims to provide a descriptive and typological analysis of a collection of ancient amphorae exhibited at the Annaba Museum, most of which date back to the Phoenician, Punic, and Roman periods. Amphorae are among the most significant archaeological finds that contribute to understanding the commercial and economic activity in the region of Hippo (modern-day Annaba), given their primary function as containers for transporting oil, wine, and grains across the Mediterranean Basin. The research is based on a meticulous morphological study of the amphorae in terms of size, shape, type of clay, manufacturing techniques, and decorative elements, in addition to identifying their discovery sites and chronological frameworks. These amphorae are classified according to well-known typologies in archaeological literature, such as the Late Punic type, the Western Roman type, and the African type, which helps trace trade routes and cultural connections between North Africa and major Mediterranean centers. The study reveals a remarkable diversity in the origins of the amphorae, reflecting Hippo’s status as an active port in antiquity. It also highlights the importance of these artifacts in reconstructing the economic and cultural history of the region. The study recommends the continuation of inventory, documentation, and laboratory analysis efforts to enhance accurate knowledge about the original contexts of these finds.